Impact of incident venous thromboembolism on risk of arterial thrombotic diseases - Lind, Caroline (UiT Norges arktiske universitet, 2015)
Background: Growing evidence support an association between venous thromboembolism (VTE) and arterial thrombotic diseases (i.e. myocardial infarction (MI) and ischemic stroke). We aimed to study the association between VTE and future arterial events, and to determine the population attributable risk (PAR%) of arterial events by VTE in a large prospective cohort recruited from the general population. Methods and Results: In 1994-1995 and 1993-1997, 81 687 subjects were included in the Tromsø Study and in the Diet, Cancer and Health Study and followed to the date of incident venous and arterial events (MI or ischemic stroke), death or migration, or to the end of the study period (2010 and 2008, respectively). There were 1 208 cases of VTE and 90 subsequent arterial events during a median follow-up of 12.2 years. An association between VTE and future arterial events was found in all women and men <65 years, but not in men >65 years. Women <65 years with VTE had 3.3-fold higher risk of arterial disease (adjusted HR 3.28, 95%CI 1.69-6.35) compared to women of the same age without VTE. The corresponding HR in men <65 years was 2.06 (95%CI: 1.32-3.20). Only 0.9% of the arterial events were attributed to VTE, and the VTE explained 63.8% of the risk of arterial events among VTE patients. Conclusions: Our findings imply that women and young men with VTE have higher risk of arterial thrombotic disease than those without VTE. However, only 1% of the arterial thrombotic events in the population are attributed to VTE.